Strategies for Overcoming Teacher Burnout in Schools; Expanding the Human Resource Management - Purnamaningsih, Ine Rahayu (JURNAL AL-TANZIM, 2023)
This study analyses human resource management in overcoming teacher burnout at SMA Negeri 1 Kota Cimahi. More and more demands from both the government and the institutions can lead to teacher burnout. This study uses a qualitative approach to the type of case study. The data was obtained from observation, interviews and documentation. The informants were selected through purposive sampling, resulting in 4 people: the principal, deputy head of curriculum, deputy head of student affairs, and subject teacher. The data analysis uses Yin's theory without any control, just observing and then explaining it. As for the results obtained, four stages in human resource management are implemented in SMA Negeri 1 Kota Cimahi: identifying, imitation, attention, and inference. Identifying is intended to recognize each character in their performance. Imitation is related to the principal's strategy in giving uswah to his subordinates. Attention is embodied in the principal's real action in involving teachers in all activities at school, and inference is related to concluding all the information collected from the initial stage to make a joint decision.